Killer Instinct / [book 2] - Barnes, Jennifer Lynn, 1983- (Quercus, 2023)
Seventeen-year-old Cassie Hobbes has a gift for profiling people. Her talent has landed her a spot in an elite FBI program for teens with innate crime-solving abilities, and into some harrowing situations. After barely escaping a confrontation with an unbalanced killer obsessed with her mother’s murder, Cassie hopes she and the rest of the team can stick to solving cold cases from a distance. But when victims of a brutal new serial killer start turning up, the Naturals are pulled into an active case that strikes too close to home: the killer is a perfect copycat of Dean’s incarcerated fathera man he’d do anything to forget. Forced deeper into a murderer’s psyche than ever before, will the Naturals be able to outsmart the enigmatic killer’s brutal mind games before this copycat twists them into his web for good? With her trademark wit, brilliant plotting, and twists that no one will see coming, Jennifer Lynn Barnes will keep readers on the edge of their seats (and looking over their shoulders) as they race through the pages of this thrilling novel.